Educational Research and Qualitative Research:: Potentialities and Challenges in Contemporary Time - de Castro, Paulo Alexandre; Guerra, Cecília; Santoro, Perseu Angelo; Barros, Victor F A (Cadernos de Educação Tecnologia e Sociedade, 2023)
Abstract. This special issue of the scientific journal "Brazilian Journal of Education, Technology and Society" (BRAJETS) presents the content of the eleven papers selected by the scientific/organizing committee of the Ibero-American Congress on Qualitative Research (CIAIQ2022 and CIAIQ2023 editions). The partnership between CIAIQ and BRAJETS aims to promote and disseminate qualitative research among the scientific community in the target areas of the Journal, which are: education, technology, medicine, society, and internationalization of postgraduate programs. The central theme of this special issue was "Educational research and qualitative research: potentialities and challenges in contemporary times". To provide quality and representativeness of the articles published in this journal, we made sure that all of them went through a double-blind review process, through careful analysis by a scientific committee composed of experienced, qualified, and very active researchers in their respective areas of expertise. In view of the above, we invite everyone to enjoy reading this special issue, and that it may contribute with inspirations and ideas for the writing and execution, whether of investigations or future works.